Clinical prediction score of nonalcoholic fatty liver disease in adolescent girls with polycystic ovary syndrome (PCOS‐HS index). (16th August 2019) - Carreau, Anne‐Marie; Pyle, Laura; Garcia‐Reyes, Yesenia; Rahat, Haseeb; Vigers, Tim; Jensen, Thomas; Scherzinger, Ann; Nadeau, Kristen J.; Cree‐Green, Melanie
Abstract: Objective: Nonalcoholic fatty liver disease (NAFLD) is common in obese adolescents with polycystic ovary syndrome (PCOS), but there are no inexpensive ways to accurately identify NAFLD in PCOS. The objective was to develop a simple clinical score to screen for NAFLD risk in obese adolescents with PCOS. Design: This is a secondary analysis of 3 cross‐sectional studies on metabolic characterization of obese adolescents with PCOS. 108 overweight and obese adolescents with PCOS (BMI > 90th percentile, age 12‐19 years) were enrolled from 2012 to 2018. Methods: Magnetic resonance imaging was used to quantify hepatic fat fraction (HFF). A development cohort of 87 girls were divided by presence of NAFLD (HFF > 5.5%). A logistic regression model with the outcome of NAFLD and candidate predictor variables was fit. A simplified model (PCOS‐HS index) was created using backwards stepdown elimination. Validation was performed using 200 bootstrapped sample and in a second cohort of 21 PCOS participants. Results: 52% of the development cohort had NAFLD. The PCOS‐HS index that included BMI percentile, waist circumference, ALT and SHBG had an AUCROC of 0.81, sensitivity 82%, specificity 69%, negative predictive value (NPV) 78% and positive predictive value 74%, using a threshold of 0.44 to predict HS. A threshold of 0.15 ruled out NAFLD with a NPV 90%. In the validation cohort, the model showed an accuracy of 81%, sensitivity of 91% and specificity of 70%. Conclusions: We developed a clinical index to identify NAFLD in girls with PCOS who would need further evaluation and treatment.